Activated FeS2@NiS2 Core–Shell Structure Boosting Cascade Reaction for Superior Electrocatalytic Oxygen Evolution. Issue 17 (3rd February 2023) - Zhang, Lulu; Rong, Ju; Yang, Yongqiang; Zhu, Huaze; Yu, Xiaohua; Chen, Chunlin; Cheng, Hui‐Ming; Liu, Gang
Abstract: Unlike single‐step reactions, multi‐step reactions can be greatly facilitated only if all the intermediate reactions can be catalyzed simultaneously and progressively. Herein, the theoretical analysis and experiments to illustrate the superiority of the cascade oxygen evolution reaction (OER) are conducted. As different OER intermediate reactions demand Fex Ni1‐x OOH with altered Fe/Ni ratios, gradient Fe‐doped NiOOH can be an ideal electrocatalyst for the efficient cascade OER in line. Fine controlling of the nucleation sequence of iron and nickel sulfides leads to a FeS2 @NiS2 core–shell structure. The activated outward diffusion of Fe dopants results in the gradient Fe/Ni ratios in the Fex Ni1‐x OOH shell, where a cascade OER can happen. Electrochemical tests suggest that the FeS2 @NiS2 only needs an overpotential of 237 mV to reach the current density of 10 mA cm −2, with fast reaction kinetics and good stability. Abstract : In ideal conditions, the continuous intermediate reactions in oxygen evolution reaction (OER) require active sites with high, moderate, and low Fe/Ni ratios, as well as gradient spatial distribution of them. Here, activating FeS2 @NiS2 core–shell structure results in a shell of Fex Ni1‐x OOH with gradient Fe/Ni ratios, thus realizing cascade OER with superior performance.